Clustering of Customer Complaints from PDAM Kota Binjai Using the K-Means Method - Lailatul Magfiroh; Hermansyah Sembiring; Anton Sihombing (International Journal of Health Engineering and Technology, 2022)
PDAM Tirtasari Binjai City is a public service institution that has a monopoly on water supply in Binjai City. The predicate as a metropolitan city, illustrates that Binjai City is a city with dense industry and trade. In this study, discusses how to handle customer complaints of PDAM Binjai City to provide satisfaction to customers. The research method used in this study is K-Means which aims to describe the quality of service for handling customer complaints at PDAM Kota Binjai in increasing customer satisfaction. The informant determination technique carried out by the researcher is using the Clustering K-Means method.